The Effect of Product Development on Operational Performance: A Case Study of Ultimate Motors - Musie Ayana Dagnaw; Fitsum Tsegaye Gebreab; Chekol Gizachew Melisew; Hailemichael woldu kiros; Kiflu Chekole Tekle; Mohamad Maulana Ridzki (Al-Makki Publisher, 2025)
This study entitled “The effect of Product Development on Operational Performance: A Case Study of Ultimate Motors Plc